2022
DOI: 10.3897/zookeys.1089.78182
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of the Mexican-endemic cavefish Ophisternon infernale (Synbranchiformes, Synbranchidae): insights on patterns of selection and implications for synbranchiform phylogenetics

Abstract: Ophisternon infernale is one of the 200+ troglobitic fish species worldwide, and one of the two cave-dwelling fishes endemic to the karstic aquifer of the Yucatán Peninsula, Mexico. Because of its elusive nature and the relative inaccessibility of its habitat, there is virtually no genetic information on this enigmatic fish. Herein we report the complete mitochondrial genome of O. infernale, which overall exhibits a configuration comparable to that of other synbranchiforms as well as of more distantly related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
2
3
0
3
Order By: Relevance
“…The loss of the D-arm in trnS is a common occurrence in fish (Mar‐Silva et al. 2022 ), and this characteristic was consistent across all Trematomus species examined in this study. However, loss of the D-arm in trnG represents a novel structural variation, initially observed in T. hansoni (while T. nicoli retains the D-arm, as per unpublished data).…”
Section: Resultssupporting
confidence: 83%
“…The loss of the D-arm in trnS is a common occurrence in fish (Mar‐Silva et al. 2022 ), and this characteristic was consistent across all Trematomus species examined in this study. However, loss of the D-arm in trnG represents a novel structural variation, initially observed in T. hansoni (while T. nicoli retains the D-arm, as per unpublished data).…”
Section: Resultssupporting
confidence: 83%
“…Wang et al [ 50 ] suggested that the size of the mitochondrial genome length in closely related species may be caused by variations in the tandem repeat elements within the CR which can explain the gene overlaps. In addition, we also found that the mitochondrial genome of S. kozlovi was composed of thirty-seven genes (thirteen PCGs, twenty-two tRNAs, two rRNAs) and an OL and a CR; the genome organization and composition of which were in accordance with those of most of fish species reported previously [ 51 , 52 , 53 ]. The AT and GC skews are a measure of asymmetry in the nucleotide composition of the mitochondrial genome.…”
Section: Discussionsupporting
confidence: 87%
“…But we also found that there are differences in the incomplete stop codons between species from distinct taxa. For example, Mar-Silva [ 51 ] analyzed the mitochondrial genome of Ophisternon infernale and found that seven PCGs had incomplete stop codons for atp6, nad5 used TA as a stop codon, and cox2, cox3, nad4, nad5, and cob employed a single T as the stop codon. However, it is assumed that the incomplete stop codons of TA or T can be modified to TAA via post-transcriptional polyadenylation [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inability of our eDNA approach to detect O. infernale in the sampled cenotes could be related to the fact that this troglobitic species, contrary to the other cave-dwelling fish inhabiting the system (T. pearsei), is extremely rare, cryptic and benthic in nature, and reportedly with very small population sizes (Arroyave et al 2019a), thus likely to shed less DNA in the water column when compared to pelagic and more abundant species. We investigated the possibility that mismatches between the 12S primers and sequence in O. infernale were driving our inability to detect the species via eDNA, but we found no such mismatches using a recently published complete mitochondrial genome for the species (Mar-Silva et al 2022). The relatively consistent detection via eDNA of the cavefish T. pearsei (Table 2) is particularly promising and demonstrates that water samples taken at the cenote surface and in the photic zone (particularly the case of cenote Xel Aktun; Ebis and Santa Maria being more cavernous cenotes) may be useful for detecting DNA from obligate cave-dwelling species.…”
Section: Discussionmentioning
confidence: 97%